BLK MKT vintage : reclaiming objects and curiosities that tell black stories - Stewart, Kiyanna; Handy, Jannah, 1986- (Black Dog & Leventhal, 2024)
"BLK MKT Vintage: Reclaiming Our Things is a visual exploration into the world and work of the highly successful vintage/antique concept shop and growing brand, BLK MKT Vintage, that expands upon the founders' vision to center, preserve, and make accessible vintage objects that tell Black stories"--